2021
DOI: 10.3345/cep.2019.01599
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive markers for esophageal varices in children with cirrhosis

Abstract: Background The diagnosis of esophageal varices (EV) is based on the findings of esophagogastroduodenoscopy (EGD), biopsy, and serum markers. Thus, noninvasive cost-effective tests through which high-risk EV children can be diagnosed are needed. Purpose This cross-sectional study aimed to identify the noninvasive markers for EV in children with liver cirrhosis. Methods A total of 98 children with liver cirrhosis were evaluated in this study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…PC, therefore, can be a predictor of the presence of EVs [26,27]. However, PC was not independently associated with EVs in the study of Rahmani P et al [28 ▪ ]. AST/ alanine transaminase ratio (ALT) (AAR) and aspartate aminotransferase to platelet ratio index (APRI) showed sensitivity 82.4% and specificity of 36.4% with a cutoff value of 1.415, and sensitivity 83.2% and specificity 50% with a cutoff value of 1.3 for predicting EVs, respectively [29].…”
Section: The Diagnosis Of Small Varicesmentioning
confidence: 87%
See 1 more Smart Citation
“…PC, therefore, can be a predictor of the presence of EVs [26,27]. However, PC was not independently associated with EVs in the study of Rahmani P et al [28 ▪ ]. AST/ alanine transaminase ratio (ALT) (AAR) and aspartate aminotransferase to platelet ratio index (APRI) showed sensitivity 82.4% and specificity of 36.4% with a cutoff value of 1.415, and sensitivity 83.2% and specificity 50% with a cutoff value of 1.3 for predicting EVs, respectively [29].…”
Section: The Diagnosis Of Small Varicesmentioning
confidence: 87%
“…Studies show that spleen size can predict varices [27,29]. However, Rahmani P et al showed, though there were differences in spleen size between patients with and without EVs in univariate analysis, there was no difference in the logistic regression analysis [28 ▪ ]. Among patients with CLDs, splenomegaly occurs at a higher frequency in patients with EVs (100%) than in patients without EVs (70.6%) (P < 0.05) [25].…”
Section: The Diagnosis Of Small Varicesmentioning
confidence: 99%
“…Therefore, the possibility to predict the presence of HRV by using a non-invasive test(s) would improve the management of patients with compensated advanced chronic liver disease (cACLD). Currently, a non-invasive blood test, that can predict the severity of portal pressure among patients with cACLD, is not established, although different biochemical tests in combination with other non-invasive tests could be useful in screening patients for the presence of HRV ( 6 , 7 ). Facing the current COVID-19 pandemics with further limited access to healthcare this approach becomes even more important.…”
Section: Introductionmentioning
confidence: 99%
“…Volume loss is characterized by reduction in the volume of intracellular fluid and is mainly associated with loss of sodium and water. 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%